Genome-wide association study in takotsubo syndrome — Preliminary results and future directions. (1st June 2017) - Eitel, Ingo; Moeller, Christian; Munz, Matthias; Stiermaier, Thomas; Meitinger, Thomas; Thiele, Holger; Erdmann, Jeanette
Abstract: Background: Takotsubo syndrome (TS) is an acute non-ischemic cardiomyopathy characterized by transient regional systolic dysfunction of the left and/or right ventricle with still unknown etiology. The aim of the current study was to conduct for the first time a genome-wide association study (GWAS) in a cohort of TS patients to identify potential genetic risk variants. Methods: This single-center study was conducted at the University Heart Center Lübeck from 2008 to 2016. DNA isolation was done according to standard protocols. Imputation of genotypes were performed at the Michigan Imputation Server (https://imputationserver.sph.umich.edu ) using the 1000G Phase 3 v5 reference panel. Results: The study population consisted of 96 TS patients (91 females, 5 males) with a mean age of 71.9 ± 10.4 years and 475 healthy controls (268 males, 207 females). The results of GWAS analysis showed several promising candidate loci (68 loci after applying threshold of p < 5 ∗ 10 − 4 and MAF > 5%). Of these 68 loci, 18 loci contained top single nucleotide polymorphisms (SNPs) that were supported by SNPs in high Linkage Disequilibrium (r2 > 0.8) with p < 10 − 3 . Two out of the 18 loci contained SNP with hits in the GWAS catalog (traits: blood pressure, thyroid stimulating hormone). Conclusion: This first GWAS analysis in a larger cohort of patients with TS showed promising preliminary results. Further intensive research efforts of international collaborators are now necessary to enable deep-phenotyping of TS patients to ultimately assess a potential genetic cause of TS.